Rasionalitas Penggunaan Obat Hiperurisemia dan Gout Artritis di Poli Penyakit dalam RSU Royal Prima Marelan - Olivia Happy Novita; Razoki Lubis; Finna Piska (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The use of drugs for hyperuricemia and gout arthritis is given for conditions that cause higher purine metabolism in the body. This study was conducted at RSU Royal Prima Marelan to determine the pattern of drug use for hyperuricemia and gout arthritis due to inflammation caused by uric acid deposits in the joints. Data collection in this study was carried out retrospectively by collecting medical records of patients with hyperuricemia and gout arthritis. The descriptive method used in this study was a cross-sectional plan. Qualitative descriptive analysis was applied to the data. Tables or narratives were used to present the data in this study. The results showed that 30 patients out of 50 were male and 20 were female. The results of the evaluation of the rationality of drug use for hyperuricemia and gout arthritis showed that patients who were given several versions of drugs with the xanthine oxidase inhibitor group 64% were allopurinol with patients with the most appropriate indications, the right patient, and the right dose of 96%.